Project management of the implementation of a cost accounting standard in Polish hospitals - Głód, Grzegorz; Głód, Wojciech (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: The main source of the health system’s problems is primarily the limited financial resources available within the system, but its efficiency is also affected by the not fully effective management of these resources. A solution to support management processes in terms of financial management is the introduced Regulation of the Minister of Health of 26 October 2020 on recommendations on the standard of cost accounting at healthcare providers. Proper implementation of this recommendation is a challenge for healthcare entities in Poland. Aim: The aim of the article is to identify key success factors related to the management of the project to implement a cost accounting standard in hospitals in Poland. A properly implemented standard is to enable support of management processes and proper financial management in the health care system at the macro level, as well as at the level of the medical entity. The first period of functioning of these regulations is an opportunity to carry out a summary in this respect. The main determinants in this area include the level of staff education, the quality of the IT system, the use of expert knowledge, training support, and the relationship between medical staff and administrative staff. Results: The research was conducted by using a survey questionnaire. On the basis of the questionnaire survey in 52 hospitals in Poland, statistical analysis was performed using basic descriptive statistics and regression analysis, which enabled the identification of key success factors for the management of the project to implement the cost accounting standard. On the basis of the analyses carried out, recommendations were made on the principles of implementing the cost accounting standard in hospitals and the directions for its effective use in management processes in the future.